Bi-atrial Thrombi in a Structurally and Functionally Normal Heart; Ticking Time Bomb - Rajbhandari, Rajib; Shah, Jageshwar Prasad; Manandhar, Sarbagya; Pradhan, Arya; Dangol, Rebika (Nepalese Heart Journal, 2023)
We report a case of bi-atrial thrombi traversing the atrioventricular valves in a 72-year-old female with multiple thromboembolic phenomena. Right atrial thrombus can be seen in patients who are immobilized for long period of time and those with deep vein thrombosis and pulmonary embolism. And the left atrial thrombus may present in a case of atrial fibrillation but not common in patients with sinus rhythm. This patient is unique having thrombus in both the atria. She initially presented with ischemic stroke. Echocardiography revealed bi-atrial clots. Later, she developed pulmonary embolism followed by acute right upper limb ischemia. The patient refused all invasive treatments and was managed with anticoagulants only. The patient responded well to therapy with complete thrombus resolution without any significant complications.